2013
DOI: 10.2319/101512-801.1
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal plane canting reduction accompanies mandibular counterclockwise rotation in camouflaging treatment of hyperdivergent skeletal Class II malocclusion

Abstract: Increased OP canting with overerupted incisors is evident in the hyperdivergent skeletal Class II malocclusion. During the camouflaging treatment, reduction of OP canting could occur. It was accompanied by mandibular counterclockwise rotation and intrusion of the maxillary incisor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 18 publications
2
32
0
2
Order By: Relevance
“…Hyperdivergent skeletal Class II malocclusion has always been an intractable challenge for orthodontic practitioners because it presents with both sagittal and vertical discrepancies. 1 To get these discrepancies corrected, favorable mandibular counterclockwise rotation during treatment is required. Many studies have pointed out that mandibular rotation is closely related to alteration of the occlusal plane; continuous horizontalization of the occlusal plane is accompanied by simultaneous reduction in its cant during growth and development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperdivergent skeletal Class II malocclusion has always been an intractable challenge for orthodontic practitioners because it presents with both sagittal and vertical discrepancies. 1 To get these discrepancies corrected, favorable mandibular counterclockwise rotation during treatment is required. Many studies have pointed out that mandibular rotation is closely related to alteration of the occlusal plane; continuous horizontalization of the occlusal plane is accompanied by simultaneous reduction in its cant during growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although the occlusal plane is a horizontal plane, its control is literally under the control of the vertical dimensions of dental arches. 1 The fact that the vertical molar height should be strictly limited to avoid unfavorable backward rotation of mandible has been widely accepted. 3 In addition, this unfavorable mandibular rotation in hyperdivergent cases could lead to a lower hyoid bone position, with subsequent reduction of the pharyngeal airway space and eventual occurrence of the obstructive sleep apnea/hypopnea syndrome (OSAHS).…”
Section: Introductionmentioning
confidence: 99%
“…Ye R et al [9] reported that the hyperdivergent skeletal Class II malocclusion in non-growing patients has a steeper cant of the occlusal plane, and an excessive height of the maxillary incisors. Successful treatment requires flattening of occlusal plane by intrusion of anterior teeth and avoiding any increase in vertical height of the molar [10].…”
Section: Discussionmentioning
confidence: 99%
“…Un punto de vista intermedio, propuesto por investigadores como Rabie et al 21,27,39,62 consideran que el cartílago condilar mandibular sirve como un importante centro de crecimiento para la mandíbula en desarrollo durante las etapas fetal y postnatal temprana; pero cuando la actividad funcional aumenta, funciona como cartílago articular. Investigaciones clínicas en las cuales se modificó la posición mandibular por compensaciones y movimientos dentales, describen el cartílago del cóndilo mandibular como un lugar de compensación de crecimiento que sigue los cambios de posición espacial de la mandíbula, donde juegan un papel importante numerosos factores intrínsecos y extrínsecos, teniendo como principio que el crecimiento cráneo-facial tiene una adaptación primaria en la función dental y una adaptación secundaria en su-turas y cartílago condilar 68,70 . Esto explica cómo una inadecuada relación cúspide-fosa, contactos prematuros y relaciones intermaxilares deficientes pueden generar constantes desequilibrios en el cóndilo mandibular, el cual responde mediante una adaptación, cambiando su forma por procesos de modelado, remodelado y desplazamiento, condicionando la rotación del plano oclusal y de la mandíbula 3,4,69 .…”
Section: Factor De Crecimiento Vascular Endotelial (Vegf)unclassified